DIAGNOSTIC ACCURACY OF MRI IN SONOGRAPHICALLY INDETERMINATE ADNEXAL MASSES - Shama Aslam; Anjum Mehdi; Murtaza Ali et al. (Journal of University Medical & Dental College, 2017)
ABSTRACT OBJECTIVES: To determine the accuracy of MRI in characterization of sonographically indeterminate adnexal masses while histopathology is taken as gold standard. Study design: Cross sectional (validation) study Duration of study: from July 2013 to December 2013 Setting: Radiology Department of Allied Hospital Faisalabad. Patient & methods: After obtaining approval from institutional ethical committee, a total of 61 patients were enrolled in this study. All the patients are examined with MR imaging performed on a 1.5-T Philips MR imaging unit in the radiology department Allied Hospital Faisalabad. The mean interval between sonography and MRI was 7 days. The final diagnosis for each of the 61 masses was established by histopathology. RESULTS: All women having a mean age of 45 years (range, 16–86 years) who were having sonographically indeterminate adnexal masses were included in the study. The mean interval between sonography and MRI was 7 days. There were 72.1% benign and 27.9% malignant cases on MRI while on histopathology 77% masses were benign and 23% malignant. The sensitivity and specificity of MRI in determining adnexal masses in our study is 100% & 93.6% Conclusion: Magnetic resonance imaging (MRI) has high contrast resolution, it provides good tissue characterization, and also capable of multiplanar imaging capabilities; it is a useful tool for diagnosis of female pelvic pathology. Magnetic resonance imaging is helpful in characterization of adnexal masses were ultrasound cannot evaluate it properly.